CURRENT PROBLEMS OF IMPLEMENTING INCLUSIVE EDUCATION IN EDUCATIONAL INSTITUTIONS OF UKRAINE AND COUNTRIES OF THE EUROPEAN UNION (Comparative Professional Pedagogy, 2023)
The article analyzes current problems of implementing inclusive education in educational institutions of Ukraine and countries of the European Union. Various specific aspects of inclusive education in European countries are highlighted. It is substantiated that there is a need to stimulate the use of the best world experience in the implementation of inclusive education in different countries. An important aspect is ensuring effective investment into inclusive education both in Ukraine and in the countries of the European Union.The purpose of the article is to analyze the experience of implementing inclusive education in the countries of the European Union and Ukraine.It is defined that the implementation of inclusive education in Ukrainian educational system has a number of urgent problems that must be solved, namely: the lack of a clear mechanism for the implementation of inclusive education; the lack of a unified approach to understanding the terms used in the process of obtaining an education by people with special educational needs; the need to introduce inclusive education at all levels of education in Ukraine; different sub-departments of educational institutions (special and general); the need to review the mechanism of state financing of educational institutions that provide inclusive educational services; introduction of broad educational work among the population regarding the necessity and positive nature of the implementation of inclusive education.Current problems of inclusive education in the European Union are as follows: increasing the quality and significance of inclusive education; increasing the number of graduates and reducing the number of people who do not graduate from educational institutions; review and preparation of educational programs that will meet the needs of people with special educational needs in education; stimulating the use of world leading experience in teaching and scientific research; providing higher education students with wider opportunities to acquire additional skills through study and internships abroad; strengthening links between inclusive education, research and business; ensuring effective investment into inclusive education.
Keywords: inclusive education; countries of the European Union; Ukraine; educational institutions; people with special educational needs